Effective enhancement in rate capability and cyclability of Li4Ti5O12 enabled by coating lithium magnesium silicate. (1st February 2019) - Bai, Xue; Zhang, Bo; Jiang, Guan-Zhong; Han, Jian-Ping; Lun, Ning; Qi, Yong-Xin; Qiu, Jun; Lu, Gui-Xia; Qian, Zhao; Bai, Yu-Jun
Abstract: In terms of the unique features of good suspensibility in water, superior absorbability, adhensivity, cation exchangeability and rapid ion diffusion channels, lithium magnesium silicate (LMSO) might be an appropriate modifier for Li4 Ti5 O12 (LTO) by simply forming coating on LTO particles. According to a series of comparative experiments performed under various conditions, when the mixture of LTO and LMSO was roasted at 700 °C to form LMSO-coated LTO, the rate properties were significantly boosted (attaining cycling capacities of 160.2, 157.8, 155.8, 151.3 and 145.5 mAh g −1 with multiplying current density from 0.1 to 1.6 A g −1 ). Upon cycling at 0.5 A g −1 for 900 cycles, a capacity of 140.6 mAh g −1 was maintained. Compared to the pristine LTO, the markedly boosted rate properties and cyclability are ascribed to the LMSO coating for suppressing grain aggregation and growth, the optimized Li + and electron transfer in electrolyte by interacting with LMSO, the enhanced electronic conductivity of LTO resulted from superficial co-doping of Mg 2+ and Si 4+, the meliorated ionic conductivity associating with the Li + diffusion channels and cation exchangeability of LMSO, as well as the diminished polarization after the modification by LMSO.